The Digital Revolution in Education: Challenges and Opportunities in the Age of Information Technology - Zamroni; Muhlisin (Cigarskruie: Journal of Educational and Islamic Research, 2024)
Digital technology has revolutionized almost all aspects of life, including the education sector. Technological advances such as computers, the internet, mobile devices and apps have significantly changed the way we learn and teach. This phenomenon is known as the digital revolution in education. This research used a descriptive qualitative method and found that the digital revolution has brought about major changes in education. Digital technology offers various benefits, such as wide access, flexibility and the possibility of global collaboration. However, there are also negative impacts to watch out for, such as access gaps and social and psychological effects. We must use digital technology wisely and responsibly to create quality and inclusive education. Technological advances bring opportunities and challenges that must be faced in the education process. Hopefully, these advancements can improve the quality of education in Indonesia, while the challenges that arise in the digitalization era can be overcome with positive solutions that solve existing problems.